2015
DOI: 10.12659/msm.892318
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and Phylogenetic Analysis of Giardia duodenalis Isolates from Turkish Children

Abstract: BackgroundGiardiasis is caused by the intestinal protozoan parasite Giardia duodenalis (synonyms: G. lamblia, G. intestinalis), which is one of the most frequent parasites that infect Turkish children. However, molecular characterization of G. duodenalis in Turkey is relatively scarce. The present work aimed at genotyping G. duodenalis isolates from Turkey using molecular techniques.Material/MethodsIn the present study, 145 fecal samples from children were collected to search for the presence of Giardia by mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…Our results also showed that AII sub-assemblage frequency was significantly higher in the 0-2 year age group while the AI was higher in children 3-6 years of age. These results corroborate results from studies reporting a higher prevalence of AII genotype in younger children 18 , 62 . The high infection rate of AII in younger children can be explained by sub-standard hygiene habits facilitating the transmission of this predominantly anthroponotic sub-assemblage.…”
Section: Discussionsupporting
confidence: 90%
“…Our results also showed that AII sub-assemblage frequency was significantly higher in the 0-2 year age group while the AI was higher in children 3-6 years of age. These results corroborate results from studies reporting a higher prevalence of AII genotype in younger children 18 , 62 . The high infection rate of AII in younger children can be explained by sub-standard hygiene habits facilitating the transmission of this predominantly anthroponotic sub-assemblage.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings revealed that individuals infected with G. duodenalis in Shiraz were infected with assemblages A and B, consistent with global reports of human giardiasis ( Feng and Xiao, 2011 ). While a previous study ( Ryan and Cacciò, 2013 ) indicated that assemblage B is more common than A worldwide, in line with our results, several studies in Iran ( Babaei et al, 2008 ; Hooshyar et al, 2017 ; Rayani et al, 2014 ), Turkey ( Tamer et al, 2015 ), Iraq ( Turki et al, 2015 ), Syria ( Skhal et al, 2017 ), Saudi Arabia ( Al-Mohammed, 2011 ), Egypt ( Helmy et al, 2009 ), Thailand ( Traub et al, 2009 ), Italy ( Cacciò et al, 2002 ), Czech Republic ( Lecová et al, 2018 ), and Ethiopia ( Gelanew et al, 2007 ) have reported a predominance of assemblage A. The discrepancies may result from the geographical distribution, the populations studied as well as the different genetic and molecular tools employed ( Hashemi-Hafshejani et al, 2022 ; Rafiei et al, 2020 ), as the impact of loci is evident in the assemblage B results in tpi [52.9% (9/17)] compared to gdh [30% (3/10)] genes in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Our ndings revealed that individuals infected with G. duodenalis in Shiraz were infected with assemblages A and B, consistent with global reports of human giardiasis [36]. While a previous study [37] indicated that assemblage B is more common than A worldwide, in line with our results, several studies in Iran [31,38,39], Turkey [40], Iraq [41], Syria [42], Saudi Arabia [43], Egypt [44], Thailand [45], Italy [46], Czech Republic [47], and Ethiopia [48] have reported a predominance of assemblage A. The discrepancies may result from the geographical distribution, the populations studied as well as the different genetic and molecular tools employed [2,3], as the impact of loci is evident in the assemblage B results in tpi [52.9% (9/17)] compared to gdh [30% (3/10)] genes in the present study.…”
Section: Discussionsupporting
confidence: 92%